Expert Views, Opinions, and Recommendations: Are Graduate-Level Nurse Practitioner Programs Offering Adequate Dermatology Preparation to Students Entering Primary Care?. Issue 5 (September 2016) - Azima, Shokoufeh
ABSTRACT: Purpose: The purpose of this study is to understand how well and to what extent nurse practitioner (NP) graduate programs prepare students to recognize and manage dermatologic conditions in the primary care setting based on the views and opinions of expert dermatology NPs, obtained through the use of an open-ended questionnaire. Background: Studies have shown that NPs practicing in primary care have difficulty recognizing, diagnosing, treating, and managing dermatologic conditions. Confusion exists concerning what and when to refer to a specialist. Few peer-reviewed articles exist pertaining to the dermatologic preparation of NP students and whether a lack of preparation precipitates this phenomenon. Aim: The aim of this study was to analyze response data to identify an emergent hypothesis to be used as a basis for further research on this topic. Methods: Eight open-ended questions were sent to 15 dermatology nurse experts, of which nine responded. They were assigned random identifiers, and their answers were interpreted using thematic analysis and emergent theory. Results: The emergent hypothesis indicated that experts in the field of dermatology nursing recognize a need for expanded dermatology preparation for NP students in graduate programs. Several reasons were provided, and recommendations were given. Discussion: Deficiencies in the level of dermatologic knowledge necessary to competently treat patients with skin conditions in primary care settings are not a phenomenon isolated to NP practice. Similar challenges are found in the literature relating to primary care physicians and physician assistants. NPs have an opportunity to be leaders in this area of clinical and didactic preparation for future practitioners. Conclusion: Expanding dermatology preparation at the graduate NP level is necessary and will improve primary care patient outcomes as well as educational standards within the NP community.